Teaching methodologies and the inclusion promotion of students with Attention Deficit Hyperactivity Disorder (ADHD): An analysis in CAPES dissertations and theses (Research, Society and Development, 2021)
Objective: This study aims to analyze works which deal with students with Attention Deficit Hyperactivity Disorder and the proposition of teaching methodologies which favor their learning and inclusion. Methodology: It is a bibliographical, qualitative and exploratory research,in which searches were carried out on Capes Theses and Dissertations Catalog database using the descriptor “Attention Deficit Hyperactivity Disorder” for the search. The time frame used on the searches was the period from 2015 to 2020. On this investigation, there were found 160 works, being 121 dissertations and 39 theses. For data analysis, it has had base on Bardin's Content Analysis. On this investigation, there has been found 160 works, from which 121 were dissertations and 39 were theses, from the abstracts readings there have been discarded duplicates and those which did not refer to the area of education, remaining 25, from which 7 were theses and 18 were dissertations, which were read in full excluding those which were not related to the teacher and inclusive practice. For the purpose of this study there were found the following practices: a) Contribution of Khan Academy on learning mathematical content, from which we verified combining games with exercises contributes to learning; b)Mobile application to help elementary school students who have ADHD on learning multiplication table; which we certified playful activities contribute to the basic mathematical content approximation; c) The narrative construction in texts produced by students with and without ADHD in which we realized creativity is essential to stimulating writing. Conclusion: The inclusive practices found in this study are extremely significant, as they indicate possible alternatives to school inclusion promotion, being necessary to disseminate them as a way of inspiration to other teachers. We emphasize further studies are essential to Brazilian Inclusive Education to advance.